2020
DOI: 10.1186/s12888-020-02864-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic- knowledge, perception, anxiety and depression among frontline doctors of Pakistan

Abstract: Background COVID-19 is a global pandemic and has become a major public health burden worldwide. With already fragile healthcare systems it can have long lasting effects in developing countries. Outbreaks especially a pandemic situation evokes fear related behaviors among healthcare professionals and there is always an increased risk of mental health disorders. Therefore, this study aims to determine knowledge and perception about this pandemic, prevalence and factors associated with anxiety/depression among fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
70
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 16 publications
12
70
5
2
Order By: Relevance
“… 1 , 33 , 34 Several systematic reviews have also indicated that numerous cross-sectional studies across the world have found a high prevalence of anxiety and depressive symptoms in healthcare workers during the pandemic as well as a correlation of worsening mental health symptoms with occupational exposure to patients infected with COVID-19. 32 , 35 38 Physicians specifically who treat COVID-19 patients in Turkey, 39 , 40 China, 1 and Pakistan 41 are similarly experiencing an increase in depression and anxiety symptoms. Furthermore, healthcare workers in Italy 42 and China 43 who treated patients with COVID-19 experienced an increase in PTSD symptomatology, with similar findings to our data.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 33 , 34 Several systematic reviews have also indicated that numerous cross-sectional studies across the world have found a high prevalence of anxiety and depressive symptoms in healthcare workers during the pandemic as well as a correlation of worsening mental health symptoms with occupational exposure to patients infected with COVID-19. 32 , 35 38 Physicians specifically who treat COVID-19 patients in Turkey, 39 , 40 China, 1 and Pakistan 41 are similarly experiencing an increase in depression and anxiety symptoms. Furthermore, healthcare workers in Italy 42 and China 43 who treated patients with COVID-19 experienced an increase in PTSD symptomatology, with similar findings to our data.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a meta-analytic review found that the prevalence of anxiety, depressive symptoms were 25.8% and 26.8%, respectively 36 . These syntheses of the previous research highlight that anxiety and depression have been highly prevalent in South Asia, which may have aggravated amid the COVID-19 pandemic due to the continued fear of infection, loss of socioeconomic opportunities, impaired the psychosocial processes, and lack of access to mental health resources and services 47,58,72 .…”
Section: Sensitivity Analysis and Publication Biasmentioning
confidence: 99%
“…Pooled prevalence of anxietyA total of 31 studies reported the prevalence of anxiety during COVID-19 in different samples from South Asian countries[46][47][48][49][50][51][52][53][54][55][56]58,59,[61][62][63][64][65][66]68,69,[71][72][73][74][75][76][77][78][79][80] . These studies used different scales to measureanxiety in respective samples, including the Generalized Anxiety Disorder 7-item (GAD-7) scale (n = 16), Depression, Anxiety and Stress Scale -21 Items (DASS-21) scales (n = 9), Hospital Anxiety and Depression Scale (HADS) (n = 4), Patient Health Questionnaire-4 (PHQ-4) (n = 1), and Self Reporting Questionnaire 20-items (SRQ-20) scale (n = 1).…”
mentioning
confidence: 99%
“…With regard to our second hypothesis, we were able to prove that greater exhaustion, greater family strain, and reduced feelings of protection impact on levels of anxiety among physicians. Other research from the developed world [ 29 ], developing countries [ 30 ], and Pakistan itself [ 31 ] corroborate that physicians are suffering from anxiety during the pandemic.…”
Section: Discussionmentioning
confidence: 82%